Assessing the Risk for Resistance and Elucidating the Genetics of Colletotrichum truncatum That Is Only Sensitive to Some DMI Fungicides - Zhang, Can; Diao, Yongzhao; Wang, Weizhen; Hao, Jianjun; Imran, Muhammad; Duan, Hongxia; Liu, Xili (Frontiers in Microbiology, 2017)
The genus Colletotrichum contains a wide variety of important plant pathogens, and C. truncatum is one of the most prevalent species of Colletotrichum on chili in China. Demethylation-inhibitor fungicides (DMIs) are currently registered chemical agents for the management of the anthracnose disease caused by Colletotrichum spp. To assess the risk for DMI resistance development, 112 C. truncatum isolates were collected from infected pepper in 13 regions of China. The sensitivity of C. truncatum isolates to five DMI fungicides was determined based on mycelial growth inhibition assay. C. truncatum was sensitive to prochloraz, epoxiconazole, and difenoconazole, but not to tebuconazole or myclobutanil. Baseline sensitivity using the 112 C. truncatum isolates was established for the first three effective DMIs. Plots of frequency had unimodal curves for prochloraz, epoxiconazole, and difenoconazole with mean (± SE) EC50 values of 0.053 ± 0.023, 1.956 ± 0.815, and 1.027 ± 0.644 µg/ml, respectively. Eleven stable DMI-resistant mutants all had lower fitness levels than their wild-type parents, suggesting a low risk of DMI resistance in C. truncatum. By inducing gene expression, CtCYP51 gene was confirmed to play a partial role in the resistance to DMIs in C. truncatum mutants. Molecular docking was used to explain the sensitivity differentiation to five DMI fungicides in C. truncatum. It showed that M376L/H373N mutations in CYP51 changed the conformation of DMIs in the binding pocket. This change prevented the formation of the Fe – N coordinate bond between the heme iron active site and tebuconazole or myclobutanil, and apparently contributed to tebuconazole and myclobutani insensitivity.